2019
DOI: 10.1017/s175173111900003x
|View full text |Cite
|
Sign up to set email alerts
|

Possible risk factors for keel bone damage in organic laying hens

Abstract: Keel bone damage (KBD) in laying hens is an important welfare problem in both conventional and organic egg production systems. We aimed to identify possible risk factors for KBD in organic hens by analysing cross-sectional data of 107 flocks assessed in eight European countries. Due to partly missing data, the final multiple regression model was based on data from 50 flocks. Keel bone damage included fractures and/or deviations, and was recorded, alongside with other animal based measures, by palpation and vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 26 publications
5
33
0
Order By: Relevance
“…Therefore, our observation is within the range reported by Bestman and Wagenaar (2014). However, Jung et al (2019) found that aviary housing and high laying performance are positively correlated with keel bone damage; therefore, the comparatively low laying performance of our floor-housed dual-purpose crosses should have resulted in less damage. With even lower laying performances of 54.5 and 54.2% in Bresse Gauloise and Bresse × NH hens, Lambertz et al (2018) found keel bone damage in only 1.1 and 13.5% of the birds.…”
Section: Animal Welfaresupporting
confidence: 87%
“…Therefore, our observation is within the range reported by Bestman and Wagenaar (2014). However, Jung et al (2019) found that aviary housing and high laying performance are positively correlated with keel bone damage; therefore, the comparatively low laying performance of our floor-housed dual-purpose crosses should have resulted in less damage. With even lower laying performances of 54.5 and 54.2% in Bresse Gauloise and Bresse × NH hens, Lambertz et al (2018) found keel bone damage in only 1.1 and 13.5% of the birds.…”
Section: Animal Welfaresupporting
confidence: 87%
“…In modern intensive production systems for laying hens, furnished cages and noncage systems have become common because of the increasing attention given to hen welfare ( Stratmann et al., 2015 , Weeks et al., 2016 ) and the ban imposed by the European Union on the traditional cage-raising system from 2012. Noncage systems allow more space for hens to practise natural behaviors ( Stratmann et al., 2015 ); however, it evidentially increases the production and management cost ( Lay et al., 2011 ) and the incidences of mortality and keel fracture ( Wilkins et al., 2004 , Rodenburg et al., 2008 , Käppeli et al., 2011 , Jung et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In comparison with aviary systems with high stocking density, the increased space allowance and free-range access in organic egg production are meant to improve the welfare of laying hens by providing them possibilities to express their species-specific behaviour. This can result in a lower incidence of maladaptive behaviours like feather pecking and cannibalism, if the hens use the outdoor area, as reported in different studies (Bestman et al 2017;Jung et al 2019). The understanding of injurious pecking, however, still needs to be improved in order to fully prevent the problem.…”
Section: Behavioural Effectsmentioning
confidence: 99%
“…However, Wnuk-Gnich et al (2016) found that broiler chickens having access to free ranging systems were characterized by a significantly lower mortality rate compared to the control birds. High levels of freerange use have been associated with a reduced incidence of keel bone fractures in laying hens (Richards et al 2012;Jung et al 2019). The literature search did not result in specific studies of the occurrence of erysipelas infections; thus, this was excluded in this review.…”
Section: Lameness Foot Pad Dermatitis and Other Diseasesmentioning
confidence: 99%
See 1 more Smart Citation